Synthesis, Characterization and Pharmacological Evaluation of Biphenyl Based 4-Thiazolidinones - Shirke, Monika; Gangthade, Monali; Chaskar, Pratip; Somani, Rakesh (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Biphenyl based 4-thiazolidinones are found to possess a wide range of activities resulting in their synthesis. Methods: Eight molecules (VIIa-VIIh) were profoundly synthesized using four step procedures. These 4-thiazolidinone derivatives were characterized by elemental analysis (CHN) and spectral (IR and 1H NMR) analysis. All the compounds were evaluated for their in vitro antimicrobial activity against one Gram negative strain (Escherichia coli) and two Gram positive strains (Bacillus subtilis and Staphylococcus aureus) and two fungal strains (Candida albicans and Aspergillus niger). Results: The results of antimicrobial studies revealed that compounds (VIIg) possessed moderate antifungal activity and compounds (VIIc and VIIe) showed good antibacterial activity against fungal and bacterial strain respectively. Conclusion: Compounds containing electron withdrawing groups (-NO2, -CI, -Br) on the aromatic ring showed improved antimicrobial activity.
Keywords: Biphenyl based 4-thiazolidinone; Antimicrobial; Antibacterial; Antifungal; Schiff's bases